HETEROCHRONIC PARABIOSIS: OLD BLOOD ATTENUATES MITOCHONDRIAL BIOENERGETICS OF YOUNG MICE. (11th November 2018) - Gonzalez-Armenta, J L; Mahapatra, G; Allison Amick, K; Li, N; Lu, B; Molina, A
Abstract: Heterochronic parabiosis has been used to study the effects of aging for decades. Parabiosis involves surgically joining two mice so that their circulatory systems are connected. Other labs have found that heterochronic parabiosis has positive effects on muscle, liver, brain, and other tissues for the old mouse. Recently, it has been shown that old blood has a greater negative effect on young mice and resulted in decreased muscle performance and neurogenesis. While it is apparent that heterochronic parabiosis has the potential to modulate function, the effects on mitochondrial bioenergetics have not been examined. In this study, mice were connected as young to young controls, old to old controls, or young to old experimental pairs (Y-O). After seven weeks, soleus muscle was collected from each mouse. The muscle fibers were separated and permeabilized for examination of mitochondrial function using high-resolution respirometry. We found that young mice in the Y-O pairs had 74% lower complex I-mediated respiration (p=0.02), 73% lower complex II-mediated respiration (p=0.01), 76% lower complex I and complex II-mediated respiration (p=0.03), and 74% lower maximum electron transfer system capacity (p=0.001). Interestingly, both parabionts in the Y-O pairs had similar respiration across all of these parameters. Old mice in the Y-O pairs did not have any significant improvements in bioenergetic capacity. These results demonstrate that there are circulating factors present in the blood of old mice can affect the metabolism of skeletal muscle. Future studies will focus on identifying circulating factors responsible for these changes for treatment of age-related decline.